Simplified gateway selection scheme for multihop relay in vehicular ad hoc network - Alawi, Mahmoud; Saeed, Rashid Abdelhaleem; Hassan Abdalla Hashim, Aisha; Alsaqour, Raed A. (Wiley-Blackwell, 2014)
Integrating vehicular ad hoc network (VANET) and universal mobile telecommunication system (UMTS) could be a promising architecture for future machine-to-machine applications. This integration can help vehicles have steady Internet connection through the UMTS network and in communicating with other vehicles. However, dead spot areas and unsuccessful handoff processes caused by the high speed of vehicles can disrupt the implementation of this kind of architecture. In this paper, a new simplified gateway selection (SGS) scheme for multihop relay in a VANET-UMTS integration network is proposed. The proposed scheme extends the coverage or/and calming of the frequent handoff process and allows vehicles to continue to be connected to the UMTS infrastructure network. An integrated simulation environment that combines VanetMobiSim and NS2 is used to simulate and evaluate the proposed scheme. The simulation results show that the SGS scheme performed better when it was implemented with ad hoc on a demand distance vector routing and destination-sequenced distance vector routing protocols. Furthermore, the SGS scheme is compared with other cluster-based gateway selections used in the previous works. The results show that our SGS scheme outperforms other cluster-based gateway selections scheme in terms of selection delay, control packet overhead, packet delivery ratio, and overall throughput.